Identification of pressure/temperature combinations for optimal pepper (Capsicum annuum) pectin methylesterase activity - Castro, Sónia Marília
Pectin methylesterase (PME) was extracted from green bell peppers and purified by affinity chromatography. The optimal pectin and salt concentrations for the PME catalysed reaction were investigated. Purified pepper PME activity was studied during combined high-pressure/temperature treatments (18–65 °C, 0.1–600 MPa) in a model system of pectin at pH 5.6. The activity of purified pepper PME showed a maximum at 200 MPa and 55 °C. A third-degree polynomial model (derived from a thermodynamic model) was successfully used to describe the heat–pressure dependence of the initial rates of purified pepper PME-catalyzed methanol formation.